Effect of bedding plane on mechanical properties, failure mode, and crack evolution characteristic of bedded rock-like specimen. (February 2023) - Liu, Hanxiang; Jing, Hongwen; Yin, Qian; Meng, Yaoyao; Zhu, Gaofang
Highlights: The existence of bedding planes significantly influences the mechanical and fracture characteristic of rock-like specimens. 3D numerical simulation was applied with cohesive element simulating the bedding planes. The mechanical and fracture properties are coupling affected by orientation angle, spacing, and strength of bedding planes. For all spacing and strength of bedding, the minimum strength and failure strain occur at 30°–60° orientation angle. Abstract: To study the influence of bedding planes on mechanical properties and failure characteristics of specimens, an experimental test was conducted first on bedded rock-like specimens by uniaxial compression test with acoustic emission and digital image correlation. Experimental results show that both uniaxial compression strength (UCS) and failure strain ( ε f ) present a tendency to first decrease and then increase with the increase in bedding angle ( α ). Moreover, the existence of bedding planes changes failure mode and fracture process of bedded specimen. Based on experimental results, three-dimensional numerical models containing bedding planes were used to determine the effect of orientation angle ( α ), spacing ( s ), and strength ( λ ) of bedding planes. Numerical results are as follows: (1) For α = 0° and 30°, the increase in s leads to the decrease in translaminar tensile crack and increase in translaminar shear crack, and the trend is reversed for α = 45° and 60°. Besides, (2) the variation of s leads to the variation of the percentage of the crack in bedding and rock matrix. However, (3) with the increase in s, the UCS and ε f of bedded specimen at the same α remain almost unchanged. Unlike the influence of s, (4) the UCS and εf of bedded rock for α = 30°–60° are positively correlated with λ . (5) Moreover, with the increase in λ, the BP-crack percentage decreases dramatically, leading to the variation of the failure mode of bedded rock.